2020
DOI: 10.1111/jcmm.15269
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of NIPBL leads to impaired RUNX1 expression and haematopoietic defects

Abstract: The transcription factor RUNX1, a pivotal regulator of HSCs and haematopoiesis, is a frequent target of chromosomal translocations, point mutations or altered gene/protein dosage. These modifications lead or contribute to the development of myelodysplasia, leukaemia or platelet disorders. A better understanding of how regulatory elements contribute to fine‐tune the RUNX1 expression in haematopoietic tissues could improve our knowledge of the mechanisms responsible for normal haematopoiesis and malignancy insur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…CTCF, along with the loop extruding factor cohesin, mediates the establishment and maintenance of both E-P interactions and TAD structure (Nora et al 2017, Rao et al 2017, Schwarzer et al 2017. Interestingly, Runx1 was mis-regulated in zebrafish after perturbation of CTCF/cohesin (Horsfield et al 2007, Marsman et al 2014, Mazzola et al 2020, suggesting that Runx1 regulation may depend on chromatin structure. Elucidating Runx1 transcriptional regulatory mechanisms is expected to contribute to a better understanding of the chromatin conformation changes employed by complex multi-promoter genes during development.…”
Section: Introductionmentioning
confidence: 99%
“…CTCF, along with the loop extruding factor cohesin, mediates the establishment and maintenance of both E-P interactions and TAD structure (Nora et al 2017, Rao et al 2017, Schwarzer et al 2017. Interestingly, Runx1 was mis-regulated in zebrafish after perturbation of CTCF/cohesin (Horsfield et al 2007, Marsman et al 2014, Mazzola et al 2020, suggesting that Runx1 regulation may depend on chromatin structure. Elucidating Runx1 transcriptional regulatory mechanisms is expected to contribute to a better understanding of the chromatin conformation changes employed by complex multi-promoter genes during development.…”
Section: Introductionmentioning
confidence: 99%
“…Since NIPBL has emerged as a potential player in myeloid cell differentiation and in the insurgence of hematological malignancies [ 21 , 22 , 23 ], we performed the functional enrichment analysis also using a collection of gene sets related to myeloid differentiation and acute myeloid leukemia (AML; Table S5 ). Interestingly, we found that a set of genes up-regulated in human hematopoietic lineage-committed progenitor cells, as compared to hematopoietic stem cells (HSC) and mature cells, were significantly activated in nipblb -MO embryos at 24 hpf.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, dysregulation of NIPBL has been associated with tumor insurgence, in particular, in hematological malignancies [ 21 , 22 , 23 ]. To further verify this association, we used a collection of gene sets related to myeloid differentiation and AML in the functional enrichment analysis of the gene expression pattern induced by nipblb loss-of-function.…”
Section: Discussionmentioning
confidence: 99%
“…It plays an indispensable role in terms of regulating Runx1 expression in a specific subpopulation of hematopoietic progenitors and cohesin together with CTCF determines the spatial distribution of runx1 transcripts in the zebrafish embryo (32,79). Monoallelic loss of Rad21 resulted in a decrease in the transcription of runx1 and micro-injection of runx1 mRNA can rescue the defects caused by RAD21 mutations in differentiated blood cells of the zebrafish model (80). Nevertheless, RNAimediated cohesin knockdown was found to enhance RUNX1 transcription in the leukemia HL60 cell line (32).…”
Section: Mechanisms Of Cohesin Gene Mutations In Leukemogenesismentioning
confidence: 99%
“…Nevertheless, RNAimediated cohesin knockdown was found to enhance RUNX1 transcription in the leukemia HL60 cell line (32). Moreover, Mazzola et al found there was no significant correlation between the expression of RAD21 and RUNX1 in both megakaryocytes derived from healthy donors and megakaryocytes derived from adult AML patients (80). These evidences indicate that cohesin performs different functions in regulating RUNX1 expression in different species.…”
Section: Mechanisms Of Cohesin Gene Mutations In Leukemogenesismentioning
confidence: 99%